The effects of obesity and weight gain in young women on obstetric outcomes. - Magriples, Urania; Kershaw, Trace S; Rising, Sharon Schindler; Westdahl, Claire; Ickovics, Jeannette R (American journal of perinatology, 2009)
We investigated body mass index (BMI) and weight gain among pregnant women (ages 14 to 25) and assessed the relationship of BMI and weight gain on birth outcomes. We performed a secondary analysis of 841 women enrolled in a randomized controlled trial receiving prenatal care in two university-affiliated clinics. Almost half the patients were overweight or obese. An average of 32.3 +/- 23.6 pounds was gained in pregnancy with only 25.3% gaining the recommended weight and over half overgaining. Weight gain had a significant relationship to birth weight. Multivariate analysis showed that prepregnancy BMI but not weight gain was a significant predictor of cesarean delivery (odds ratio [OR] 1.91, confidence interval [CI] 1.24 to 2.69, P < 0.0001). When large-for-gestational-age infants were removed from the analysis, there was still a significant effect of BMI on cesarean delivery (OR 1.76, CI 1.17 to 2.66, P = 0.007) but not of weight gain (OR 1.45, CI 0.94 to 2.17, P = 0.093). Prepregnancy BMI is a more significant predictor of cesarean delivery than pregnancy weight gain in young women.
Keywords: Adolescent; Adult; Birth Weight; Body Mass Index; Causality; Cesarean Section; Connecticut; Female; Georgia; Humans; Obesity; Obstetric Labor Complications; Odds Ratio; Pregnancy; Pregnancy Complications; Pregnancy Outcome; Prospective Studies; Weight Gain; Young Adult